The Radiological Evaluation of Mandibular Canal Related Variables in Mandibular Third Molar Region: a Retrospective Multicenter Study - Dogukan Yilmaz; Emel Tuğba Ataman-Duruel; Zehra Beycioğlu; Samir Goyushov; Tansu Çimen; Onurcem Duruel; Tolga Fikret Tözüm (Stilus Optimus, 2022)
Objectives: The aim of this retrospective study was to investigate anatomical structure of mandibular canal and the factors those increase the possibility of inferior alveolar nerve damage in mandibular third molar region of Turkish population. Material and Methods: Overall 320 participants with 436 mandibular third molars were included from four different study centers. Following variables were measured: type and depth of third molar impaction, position of mandibular canal in relation to third molars, morphology of mandibular canal, cortication status of mandibular canal, possible contact between the third molars and mandibular canal, thickness and density of superior, buccal, and lingual mandibular canal wall, bucco-lingual and apico-coronal mandibular canal diameters on cone-beam computed tomography scans. Results: Lingual mandibular canal wall density and thickness were decreased significantly as the impaction depth of mandibular third molar was increased (P = 0.045, P = 0.001 respectively). Highest buccal mandibular canal wall density and thickness were observed in lingual position of mandibular canal in relation to mandibular third molar (P = 0.021, P = 0.034 respectively). Mandibular canal with oval/round morphology had higher apico-coronal diameter in comparison to tear drop and dumbbell morphologies (P = 0.018). Additionally, mandibular canals with observed cortication border and no contact with mandibular third molar had denser and thicker lingual mandibular canal wall (P = 0.003, P = 0.001 respectively). Conclusions: Buccal and lingual mandibular canal wall density, thickness and mandibular canal diameter may be related with high-risk indicators of inferior alveolar nerve injury.